Making sense of spirituality - Hayes, Steven C (Perspectivas em Análise do Comportamento, 2020)
In ordinary language a clear distinction is made between the world of matter and that of spirit. While dualism is typically thought to be incompatible with behaviorism, a behavioral analysis of self-awareness suggests that there are good reasons for dualistic talk. Reputed qualifies of both the spiritual aspect of humans and of a metaphysical God seem to flow naturally from the analysis. The use of the spiritual facet of self in therapy is briefly discussed.